Measurement of the differential inclusive B+ hadron cross sections in pp collisions at s=13 TeV - Khachatryan, Vardan; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier BV, 2017)
The differential cross sections for inclusive production of B+ hadrons are measured as a function of the B+ transverse momentum pT B and rapidity yB in pp collisions at a centre-of-mass energy of 13 TeV, using data collected by the CMS experiment that correspond to an integrated luminosity of 48.1 pb−1. The measurement uses the exclusive decay channel B+→J/ψK+, with J/ψ mesons that decay to a pair of muons. The results show a reasonable agreement with theoretical calculations within the uncertainties.